2007
DOI: 10.1111/j.1601-0825.2006.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the levels of immunoglobulins in the saliva of diabetic individuals with periodontitis using checkerboard immunodetection

Abstract: Checkerboard immunodetection was reliable and economical for screening saliva samples for multiple antibody reactions. Our results support previous reports which suggested that patients with periodontitis are able to secrete high levels of salivary Ig, but are hampered in targeting their salivary response toward A. actinomycetemcomitans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
(37 reference statements)
0
14
0
1
Order By: Relevance
“…27 Determination of possible alterations in whole saliva composition may be helpful for understanding the increased severity of PD in diabetic patients, as well as for diagnosing possible variations and defective host immune responses, including the secretion of s-IgA. 6,28 The predominance of low s-IgA values in diabetics that we observed may be related to the fact that to be effective, antibodies require the cooperation of other host-protective mechanisms. In DM patients, other immune components, such as polymorphonuclear leukocytes, are not fully functional.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…27 Determination of possible alterations in whole saliva composition may be helpful for understanding the increased severity of PD in diabetic patients, as well as for diagnosing possible variations and defective host immune responses, including the secretion of s-IgA. 6,28 The predominance of low s-IgA values in diabetics that we observed may be related to the fact that to be effective, antibodies require the cooperation of other host-protective mechanisms. In DM patients, other immune components, such as polymorphonuclear leukocytes, are not fully functional.…”
Section: Discussionmentioning
confidence: 86%
“…3,4 In this context, analysis of whole saliva provides a simple and non-invasive method of evaluating the role of salivary IgA (s-IgA) levels in PD. [5][6][7] s-IgA represents the first line of defense against pathogens that colonize and invade mucosal surfaces, thus interfering with the development of PD at a very early, but very critical, stage. 8 Studies have suggested a protective role for s-IgA in patients with PD, 5,9,10 and low concentrations of s-IgA have been associated with severe forms of this disease.…”
mentioning
confidence: 99%
“…These findings are probably associated with the elevated levels of specific anti- S. mutans and anti-insulin antibody levels also observed in these patients. The determination of changes in whole saliva composition may be used to diagnose possible variations and defective host immune responses, including the secretion of s-IgA [ 22 ]. Similar results have been reported in other studies evaluating the salivary production of IgA antibodies in diabetic patients [ 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 This is compatible with other findings showing that s-IgA levels were significantly higher in diabetic patients with periodontitis. 10,18,26 Using the gingival and modified sulcus bleeding indices, Malicka et al reported that the periodontal status of diabetic patients was significantly worse than that of healthy subjects. 12 Ranadheer et al showed that s-IgA levels were significantly higher among individuals with more than three DMFT.…”
Section: Discussionmentioning
confidence: 99%